Historical and philosophical assumptions for the formation of the exegetical paradigm of Martin Luther - Prilutskii, Alexander (Bogoslovskie razmyšlenija, 2003)
The exegesis of Martin Luther, on the one hand, is part of the reform program of the medieval church, and for this reason is included in the general confessional paradigm of the Reformation. On the other hand, Luther’s exegesis was influenced by the full range of historical and philosophical factors that determined the development of the majority of medieval intellectual movements. Obviously, one cannot correctly understand the Reformation, which is a phenomenon of the exegesis of Martin Luther, and its questions, without considering the historical and philosophical context of the late medieval period.